2022
DOI: 10.1007/s00520-022-06893-y
|View full text |Cite
|
Sign up to set email alerts
|

Barriers and facilitators to exercise among adult cancer survivors in Singapore

Abstract: Purpose Exercise can help cancer survivors manage sequela, treatment side effects, improve overall quality of life, and is recommended for most. The purpose of this study was to investigate exercise behavior and factors influencing exercise engagement among cancer survivors at the National Cancer Centre, Singapore (NCCS). Methods This cross-sectional study was inclusive of survivors of all cancer types and stages who were at least 21 years of age and had u… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 14 publications
(11 citation statements)
references
References 44 publications
(94 reference statements)
0
11
0
Order By: Relevance
“…Estimates of cancer survivors who meet PA guidelines range from about 10 to 30% [ 17 ]. Research has identified that barriers to exercise include cancer-related symptoms, low mood, time limitations, low exercise literacy, low awareness of exercise benefits, and lack of advice or referral from a health care practitioner (HCP) [ 18 21 ]. Other influential factors include sociodemographic and clinical variables, obesity, smoking, alcohol consumption, attitudes towards exercise, self-efficacy, and intentions [ 22 24 ].…”
Section: Introductionmentioning
confidence: 99%
“…Estimates of cancer survivors who meet PA guidelines range from about 10 to 30% [ 17 ]. Research has identified that barriers to exercise include cancer-related symptoms, low mood, time limitations, low exercise literacy, low awareness of exercise benefits, and lack of advice or referral from a health care practitioner (HCP) [ 18 21 ]. Other influential factors include sociodemographic and clinical variables, obesity, smoking, alcohol consumption, attitudes towards exercise, self-efficacy, and intentions [ 22 24 ].…”
Section: Introductionmentioning
confidence: 99%
“…Notably, the medical system is not trustworthy for Black/AA patients due to centuries of neglect and abuse [ 4 , 29 ]. Thus, while research has indicated that oncology healthcare providers are a preferred source of PA encouragement among cancer survivors, this research has been largely conducted with White [ 30 , 31 ] and Asian participants [ 9 ]. Findings from this study indicate that the role of family members may be especially important in PA interventions for Black/AA cancer survivors.…”
Section: Discussionmentioning
confidence: 99%
“…Physical activity (PA) is widely recommended for cancer survivors to ameliorate many of these adverse effects [ 7 ]. However, most survivors do not engage in PA at recommended levels [ 8 , 9 ]; furthermore, Black/AA survivors are less physically active than White survivors [ 10 , 11 ]. To achieve health equity for Black/AA cancer survivors, focused efforts are needed to increase PA among this population.…”
Section: Introductionmentioning
confidence: 99%
“…For example, self-managed physical activity options were the second most favourable option. Costs of gym memberships have previously been identified as a barrier for people affected by cancer [58][59][60], and home-based programmes provide a no-cost option.…”
Section: Exercise Options and Training/experience Of Exercise Staffmentioning
confidence: 99%